Prenatal Progestin Exposure Is Associated With Autism Spectrum Disorders - Li, Ling; Li, Min; Lu, Jianping; Ge, Xiaohu; Xie, Weiguo; Wang, Zichen; Li, Xiaoling; Li, Chao; Wang, Xiaoyan; Han, Yan; Wang, Yifei; Zhong, Liyan; et al. (Frontiers in Psychiatry, 2018)
We have previously reported that prenatal progestin exposure induces autism-like behavior in offspring through ERβ (estrogen receptor β) suppression in the brain, indicating that progestin may induce autism spectrum disorders (ASD). In this study, we aim to investigate whether prenatal progestin exposure is associated with ASD. A population-based case-control epidemiology study was conducted in Hainan province of China. The ASD children were first screened with the Autism Behavior Checklist (ABC) questionnaire, and then diagnosed by clinical professionals using the ASD diagnosis criteria found in the Diagnostic and Statisti¬cal Manual of Mental Disorders, Fifth Edition (DSM-V). Eventually, 235 cases were identified as ASD from 37863 children aged 0-6 years old, and 682 matched control subjects with typically developing children were selected for the analysis of potential impact factors on ASD prevalence using multivariate logistic regression. Our data show that the ASD prevalence rate in Hainan is 0.62% with a boy:girl ratio of 5.4:1. Interestingly, we found that the following factors are strongly associated with ASD prevalence: use of progestin to prevent threatened abortion, taking progestin contraceptives when conception occurs, and prenatal consumption of progestin-contaminated seafood during the first trimester of pregnancy. All the above factors are directly or indirectly involved with prenatal progestin exposure. In addition, we conducted in vivo experiments in rats. Either endogenous (progesterone) or synthetic progestin (norethindrone)-treated seafood zebrafish were used to feed pregnant dams, and the subsequent offspring showed autism-like behavior, which further demonstrated that prenatal progestin exposure may induce ASD. We conclude that prenatal progestin exposure may be associated with ASD development.